2017
DOI: 10.1111/sjop.12420
|View full text |Cite
|
Sign up to set email alerts
|

Parent–child interactions during traditional and interactive media settings: A pilot randomized control study

Abstract: Parent-child interactions are pivotal for children's socioemotional development, yet might suffer with increased attention to screen media, as research has suggested. In response, we hypothesized that parent-child play on a tablet computer, as representative of interactive media, would generate higher-quality parent-child interactions than toy play or watching TV. We examined the emotional availability of mothers and their 2-year-old child during the previous three contexts using a randomized crossover design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 38 publications
(102 reference statements)
0
29
0
3
Order By: Relevance
“…Data were extracted and synthesized from ten quantitative studies (Beyens & Beullens, 2016; Griffith & Arnold, 2019; Ho, Lee, Wood, Kassies, & Heinbuck, 2018; Krcmar & Cingel, 2014; Munzer et al, 2019; Neumann, 2018a; Rees et al, 2017; Skaug et al, 2018;Strouse & Ganea, 2017; Yuill & Martin, 2016) into Table 2. Additionally, results from two qualitative studies (Hiniker et al, 2018; Sobel et al, 2017) were extracted into Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Data were extracted and synthesized from ten quantitative studies (Beyens & Beullens, 2016; Griffith & Arnold, 2019; Ho, Lee, Wood, Kassies, & Heinbuck, 2018; Krcmar & Cingel, 2014; Munzer et al, 2019; Neumann, 2018a; Rees et al, 2017; Skaug et al, 2018;Strouse & Ganea, 2017; Yuill & Martin, 2016) into Table 2. Additionally, results from two qualitative studies (Hiniker et al, 2018; Sobel et al, 2017) were extracted into Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…These findings lend support to existing research documenting the importance of parent-child interaction and the reduction in preschool children's screen time. [10][11][12][14][15][16][17]20,22 It seems that in addition to the attractiveness of digital devices for children, lack of parental skills is one of the important factors for extreme exposure of children to digital devices. When parents are not sensitive, responsive, and available, the child is more occupied with digital devices.…”
Section: Discussionmentioning
confidence: 99%
“…14 Similarly, the child's attention is also attracted to the appealing visual and auditory effects of these devices. 11,12,15 Mendelsohn et al have shown that child exposure to digital devices reduces parent-child verbal interaction. 16 Nathanson and Rasmussen studied the impact of watching television compared to reading books and playing games on the interaction between mother and children aged 16 to 72 months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents are reported to have both positive and negative attitudes about young children using screens (Kostyrka-Allchorne et al 2017;McCloskey et al 2018;Zabatiero et al 2018). Positive ideas relate to interactive child games potentially encouraging positive parent-child interactions (Skaug et al 2017) and potentially enhancing learning (Radesky et al 2015) but increased screen use may have negative effects on social interactions (Hinkley et al 2018). Similarly early childhood educators have both positive and negative attitudes about screen use by young children, recognizing the potential to enhance learning and the potential for harm (Zabatiero et al 2018).…”
mentioning
confidence: 99%